1964
DOI: 10.1113/jphysiol.1964.sp007485
|View full text |Cite
|
Sign up to set email alerts
|

The mechanics of human saccadic eye movement

Abstract: In the investigation of oculomotor systems and especially in the mathematical descriptions of them as pursuit, tracking and stabilizing systems, the need arises for a more exact knowledge of the mechanics of the eyeball, the extraocular muscles and the supporting tissues of the orbit, particularly of the way in which these factors permit the globe to respond to the efferent discharges arising in the oculomotor nuclei. In 1954 Westheimer proposed that the eye moved in a saccade by the application of a step func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
390
0
4

Year Published

1966
1966
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 812 publications
(425 citation statements)
references
References 6 publications
31
390
0
4
Order By: Relevance
“…In Carpenter's experiments, it appeared that the high-frequency asymptote of the v.o.r. was being determined by the viscous forces in the orbital mechanics; these possess a corner frequency of 1 1 Hz (Robinson, 1964). There is no obvious explanation for this effect of decerebration on the v.o.r.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Carpenter's experiments, it appeared that the high-frequency asymptote of the v.o.r. was being determined by the viscous forces in the orbital mechanics; these possess a corner frequency of 1 1 Hz (Robinson, 1964). There is no obvious explanation for this effect of decerebration on the v.o.r.…”
Section: Discussionmentioning
confidence: 99%
“…Robinson (1964) has shown that the viscous elements in the orbit begin to impose phase lag into the eye's force-movement relationship in the same frequency range, 0*5-1*0 Hz, as that in which canal neurones display phase lead. If the brain stem path of the v.o.r.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The connective tissue of the oculomotor plant is a viscoelastic structure [18], which can be represented by a small number of Voigt elements in series [6], [7], as described in Fig. 4.…”
Section: B Modeling 1) Model Structurementioning
confidence: 99%
“…Conceptually, bioengineering approaches, using systems analytical techniques, were combined with anatomical and physiological data, to develop biologically plausible models, replacing the Bblack box^approach to neural modeling. The involvement of bioengineers in eye movement research, exemplified by David A Robinson, enticed basic and clinical neuroscientists to adopt the Bengineering approach^to understanding normal brain function and human disease [27,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47].…”
mentioning
confidence: 99%